2010
DOI: 10.1007/s11523-010-0163-4
|View full text |Cite
|
Sign up to set email alerts
|

Activity and safety of erlotinib as second- and third-line treatment in elderly patients with advanced non-small cell lung cancer: a phase II trial

Abstract: Erlotinib is an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor. Efficacy of this drug was documented in the BR.21 trial showing that adenocarcinoma, female gender, Asian ethnicity and never-smoker status are predictive of clinical response to erlotinib. Retrospective studies documented the same benefits for elderly patients as young patients in terms of response, progression-free survival, and overall survival. The primary aim of our trial was to confirm these findings in a prospective way; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…This study showed a DCR of 65% and 9.5-month median OS in the elderly group, and there was no significant difference in outcome and toxicity between elderly and younger patients [8]. An EGFR TKI such as erlotinib and gefitinib also showed an improved survival and a favorable response rate [3,10]. In the present study, GV combination chemotherapy was not inferior to the salvage regimens described above in elderly patients, and all patients were previously treated with taxane, pemetrexed or EGFR TKI, as previously mentioned.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This study showed a DCR of 65% and 9.5-month median OS in the elderly group, and there was no significant difference in outcome and toxicity between elderly and younger patients [8]. An EGFR TKI such as erlotinib and gefitinib also showed an improved survival and a favorable response rate [3,10]. In the present study, GV combination chemotherapy was not inferior to the salvage regimens described above in elderly patients, and all patients were previously treated with taxane, pemetrexed or EGFR TKI, as previously mentioned.…”
Section: Discussionmentioning
confidence: 95%
“…In those patients, salvage therapy has been shown to improve survival compared with the best supportive care alone [6,7]. Although the majority of patients enrolled in a salvage trial were younger, several data for salvage treatment have been reported in elderly patients [3,8,9,10,11]. These studies demonstrated that there were no differences in the efficacy of salvage chemotherapy between elderly and nonelderly patients, and old age itself should not be a contraindication for salvage chemotherapy [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient characteristics (all, <75 years and ≥75 years of age). ≥65 years) Italian patients with advanced NSCLC (n=31), the ORR was 16% (6). We hypothesized that the higher ORR in our study reflects the inclusion of a higher proportion of patients with EGFR mutation-positive tumors.…”
Section: Discussionmentioning
confidence: 80%
“…Erlotinib, an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), is an effective standard second-line treatment for NSCLC, regardless of EGFR mutation status (4)(5)(6)(7)(8). In a previous phase III study (BR.21), erlotinib prolonged overall survival (OS) and progression-free survival (PFS) compared with placebo when used as secondor third-line treatment of NSCLC; the OS was 6.7 and 4.7 months [hazard ratio (HR)= 0.61; P<0.001) and the PFS was 2.2 and 1.8 months (HR= 0.70; P<0.001) in the erlotinib and placebo groups, respectively (4).…”
Section: Introductionmentioning
confidence: 99%